Bina Amr' Ma'n Al-Amr Wa Al-Nahi DirÄsah Nahwiyyah Taba'Ätih Al-Fiqhiyyah - Hasbullah; Muhammad Syamsuddin Noor (UIN ANTASARI, 2025)
The study of amr (command) and nahy (prohibition) occupies a significant position in both Arabic linguistics and Islamic legal theory (uá¹£Å«l al-fiqh). Traditionally, these two concepts have often been examined separately: grammar (naá¸¥w) emphasizes structural forms, while uá¹£Å«l al-fiqh focuses on normative implications. This separation has created a methodological gap in interpreting Islamic law. The present study aims to integrate these perspectives in order to achieve a more comprehensive understanding. This research employs a qualitative method through a library research approach. Primary sources include classical works of grammar such as Ibn HishÄmâ€™s MughnÄ« al-LabÄ«b and works of uá¹£Å«l al-fiqh such as al-GhazÄlÄ«â€™s al-Mustaá¹£fÄ and al-ShÄá¹ibÄ«â€™s al-MuwÄfaqÄt. The analysis identifies the grammatical forms of amr and nahy and then explores their legal implications within the framework of uá¹£Å«l principles. The findings indicate that amr, in grammatical terms, is characterized by the imperative verb (fiÊ¿l al-amr), while nahy is marked by the prohibitive particle lÄ al-nÄhiyah attached to the present tense verb (fiÊ¿l al-muá¸ÄriÊ¿). In uá¹£Å«l al-fiqh, the default meaning of amr is obligation (wujÅ«b), and nahy is prohibition (taá¸¥rÄ«m). However, these meanings may shift to recommendation (sunnah), permissibility (ibÄá¸¥ah), or reprehensibility (karÄhah) if supported by strong contextual or textual evidence (qarÄ«nah). These results highlight the importance of integrating grammar and uá¹£Å«l al-fiqh to ensure the precision of legal derivation.